What can two years of monitoring tell us about Venezuelan coral reefs? The Southern Tropical America node of the Global Coral Reef Monitoring Network (STA-GCRMN) - Aldo Cróquer; Denise Debrot; Eduardo Klein; Martina Kurten; Sebastian Rodríguez; Carolina Bastidas (Revista de Biología Tropical, 2010)
In spite of their economic importance, coral reef communities of the world are rapidly decreasing, and an adequate management planification is needed. The benthic and fish communities of Dos Mosquises Sur and Madrizquí at Los Roques National Park, and Caiman and Cayo Norte at Morrocoy National Park, in Venezuela were monitored during 2003 and 2004. The CARICOMP method was used to describe the benthic community, and the AGRRA protocol was applied to the fish community assessment. The benthic cover of five broad living categories (i.e. corals, algae, sponge and octocorals) differed across the sites (Nested ANOVA, p < 0.05), but there were no statistical differences between parks. Despite being on different parks, the benthic cover in Dos Mosquises Sur and Cayo Norte was similar (76% based on Bray-Curtis), whereas Caiman differed greatly (57- 68%) from all other sites. The cover of hard coral, algae, sponges and octocorals was similar between 2003 and 2004 in all four sites. Similarly, the fish community structure of both parks did not change over time, and was dominated by herbivores (Pomacentridae, Scaridae and Acanthuridae). However, commercially important carnivores (e.g. Lutjanids and Serranids) were more abundant in Los Roques than in Morrocoy. Although it was expected that the benthic cover and fish community would reflect greater differences between Los Roques and Morrocoy, only the fish community appeared healthier in Los Roques, whereas Cayo Norte (Morrocoy), had a coral cover similar or higher than both sites of Los Roques. Thus, our results suggest that in Venezuela, oceanic reef sites are not necessarily ‘healthier’ (i.e. higher coral cover) than land-influenced coral communities. The addition of three new sites and the reincorporation of Caiman has improved and expanded the monitoring capabilities in Venezuela and it represents the first step towards the consolidation of a coral reef monitoring program for the country. Rev. Biol. Trop. 58 (Suppl. 1): 51-65. Epub 2010 May 01. En este estudio se describe la condición de las comunidades bentónicas e ictícolas en cuatro arrecifes que fueron monitorizados durante 2003 y 2004 en Venezuela: Dos Mosquises Sur y Madrizquí en el Parque Nacional Archpiélago Los Roques y Caimán y Cayo Norte en el Parque Nacional Morrocoy. Para ello, empleamos los protocolos de CARICOMP y AGRRA para describir la comunidad bentónica e ictícola, respectivamente. La cobertura de los cinco principales grupos bentónicos difirió entre arrecifes (ANOVA anidado, p < 0.05) más no entre parques. A pesar de pertenecer a diferentes parques la estructura de la comunidad bentónica entre Dos Mosquises Sur y Cayo Norte mostró un índice de similitud (Bray-Curtis) de 76%, mientras que Caiman difirió entre 57 y 68% con respecto a todos los arrecifes. Como se esperaba, la cobertura coralina, algas esponjas y octocorales no cambió entre 2003 y 2004. De forma similar, la comunidad de peces tampoco cambió en el tiempo y estuvo dominada por especies de herbívoros (Pomacentridae, Scaridae and Labridae). Sin embargo, en Los Roques los carnívoros de importancia comercial (e.g. lutjanidos y serranidos) fueron más abundantes que en Morrocoy. Aunque se esperaba encontrar diferencias en la comunidad bentónica e ictícola de Los Roques y Morrocoy, solo la de peces reflejó las diferencias, encontrándose en mejor estado de salud en Los Roques, mientras que CNOR, localizado en Morrocoy, presentó una cobertura similar o ligeramente mayor que los arrecifes localizados en Los Roques. Por lo tanto, los resultados de este estudio muestran que los arrecifes oceánicos no necesariamente se encuentran en mejor estado que los costeros. La inclusión de 3 nuevos sitios y la reincorporación de Caimán ha expandido y mejorado las capacidades de monitoreo de Venezuela y representa el primer paso hacia la creación de un sistema de monitoreo de arrecifes en el país.